Towards the third millenium [videorecording] the medium-term Philippine development plan - Philippines. National Economic and Development Authority ([Pasig City] NEDA)
Tackles the objectives and components of Philippines 2000 ; the steps of becoming a newly industrializing economy.
VHS.
Keywords: Philippines -- Economic policy, 2000.; Philippines -- Development plan; Philippines -- Social policy, 2000.